Prevalence and Molecular Epidemiological Data on Dirofilaria immitis in Dogs from Northeastern States of India. (21st January 2015) - Borthakur, Sonjoy Kumar; Deka, Dilip Kumar; Islam, Saidul; Sarma, Dilip Kumar; Sarmah, Prabhat Chandra
Abstract : The aim of the present study was to determine the prevalence of Dirofilaria immitis in stray, pet, and working dogs (n = 413, 266, and 103, resp.) from Guwahati (Assam) and Aizawl (Mizoram), areas located in two Northeastern States of India. Diagnostic methods applied were microscopy (wet film and Knott's concentration technique), immunological test (Ag ELISA by SNAP 4Dx ELISA kit), and molecular tools (polymerase chain reaction and sequencing), which evidenced 11.38, 18.03, and 13.93% of positive animals, respectively. No significant differences were observed by area (18.23% versus 17.68%) nor by sex (18.1% versus 17.9%), whereas stray dogs proved more infected than other groups (P < 0.05 ). ELISA test evidenced an overall 22.69% of occult infections, mainly in working dogs (60%), and molecular techniques detected Dirofilaria (Nochtiella) repens in 4 stray dogs from Guwahati. Characterization of D. immitis isolates for ITS-2 region showed close identity with South Asian isolates.